IDENTIFIKASI ANTOSIANIN BUAH DUWET (Syzygium cumini) MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI - DIODE ARRAY DETECTION [Identification of Anthocyanins in Jambolan Fruit (Syzygium cumini) by High Performance Liquid Chromatography - Diode Array Detecti - Puspita Sari; Christofora Hanny Wijaya; Dondin Sajuthi; Unang Supratman (Jurnal Teknologi dan Industri Pangan, 2009)
The aim of this study was to determine the content of total monomeric anthocyanins and to identify the anthocyanin composition of jambolan fruit (Syzygium cumini) growing in Indonesia. Anthocyanins were extracted with methanol containing 0.1% HCl, removed from non-polar impurities by partition with chloroform and purified in a C18 solid phase cartridge. Anthocyanins were identified by high-performance liquid chromatography with diode array detection (HPLC-DAD), UV-visible spectral analysis, and physico-chemical reactions. Using pH-differential method, it was known that the content of total monomeric anthocyanin in the ripe fruit was 161 mg/100 g fresh fruit (731 mg/100 g skin on wet basis or 3430 mg/100 g skin on dry basis), based on cyanidin-3-glucoside. Furthermore, five anthocyanins without acylating groups were identified as 3,5-diglucoside derivatives of delphinidin (41.29%), petunidin (27.79%), malvidin (25.60%), cyanidin (4.19%), and peonidin (1.13%). These results demonstrate that the skin of jambolan fruit especially the ripe one is rich in anthocyanin, with wide range in anthocyanidin backbone (five aglycons).